2017
DOI: 10.1007/s12035-017-0596-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced CaM Kinase II and CaM Kinase IV Activities Underlie Cognitive Deficits in NCKX2 Heterozygous Mice

Abstract: Among five members of the K-dependent Na/Ca exchanger (NCKX) family (NCKX1-5), only NCKX2 is highly expressed in mouse brain. NCKX2 in plasma membranes mediates cytosolic calcium excretion through electrogenic exchange of 4 Na for 1 Ca and 1 K. Here, we observed significantly decreased levels of NCKX2 protein and mRNA in the CA1 region of APP23 mice, a model of Alzheimer's disease. We also found that, like APP23 mice, heterozygous NCKX2-mutant mice exhibit mildly impaired hippocampal LTP and memory acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Preference DE genes in this subnetwork include gria3 , a member of the AMPA glutamate receptor family known to be an important component of the female preference response50. Also scn2a and scn8a , which are known to have molecular functions in brain circuits that mediate specific behaviors51, agap3 , involved in signal transduction, syn1 , known to be involved in synaptic plasticity and social behavior52, baz2a , which regulates transcription of androgen receptors, and slc24a2 , a critical gene in signal transduction53 with known roles in cognition and memory54, and a target of the immediate early gene fosl1 . The network structure reveals these genes are connected to other known components of the female preference transcriptional response3,18, including neuroligin-2, neuroligin-3, stmn2a & stmn2b .…”
Section: Resultsmentioning
confidence: 99%
“…Preference DE genes in this subnetwork include gria3 , a member of the AMPA glutamate receptor family known to be an important component of the female preference response50. Also scn2a and scn8a , which are known to have molecular functions in brain circuits that mediate specific behaviors51, agap3 , involved in signal transduction, syn1 , known to be involved in synaptic plasticity and social behavior52, baz2a , which regulates transcription of androgen receptors, and slc24a2 , a critical gene in signal transduction53 with known roles in cognition and memory54, and a target of the immediate early gene fosl1 . The network structure reveals these genes are connected to other known components of the female preference transcriptional response3,18, including neuroligin-2, neuroligin-3, stmn2a & stmn2b .…”
Section: Resultsmentioning
confidence: 99%
“…Some enzymes, including CaMKII, are calcium dependent. We here checked the CaMKII/CREB pathway, which is directed to learning and memory [ 24 ]. Western blots showed that high salt diet markedly decreased the expression of phosphorylated- CaMKII at (Thr286) in hippocampus of rats, but did not change the level of total CaMKII (Figure 4D , 4E and 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…These environmental microbes are found primarily in water and soil. Possible route of transmission includes direct exposure to aerosolized water or soil containing NTM species [25]. The interaction between host immune system and the pathogenicity of the organisms plays a key role in disease susceptibility [6].…”
Section: Introductionmentioning
confidence: 99%